Mid-Miocene to Present Upper-Plate Deformation of the Southern Cascadia Forearc: Effects of the Superposition of Subduction and Transform Tectonics - McKenzie, Kirsty A.; Furlong, Kevin P.; Kirby, Eric (Frontiers in Earth Science, 2022)
The southern Cascadia forearc undergoes a three-stage tectonic evolution, each stage involving different combinations of tectonic drivers, that produce differences in the upper-plate deformation style. These drivers include subduction, the northward migration of the Mendocino triple junction (MTJ) and associated thickening and thinning related to the Mendocino Crustal Conveyor (MCC) effect, and the NNW translation of the Sierra Nevada-Great Valley (SNGV) block. We combine geodetic data, plate reconstructions, seismic tomography and topographic observations to determine how the southern Cascadia upper plate is deforming in response to the combined effects of subduction and NNW-directed (MCC- and SNGV-related) tectonic processes. The location of the terrane boundaries between the relatively weak Franciscan complex and the stronger KMP and SNGV block has been a key control on the style of upper-plate deformation in the southern Cascadia forearc since the mid-Miocene. At ~15 Ma, present-day southern Cascadia was in central Cascadia and deformation there was principally controlled by subduction processes. Since ~5 Ma, this region of the Cascadia upper plate, where the KMP lies inboard of the Franciscan complex, has been deforming in response to both subduction and MCC- and SNGV-related effects. GPS data show that the KMP is currently moving to the NNW at ~8-12 mm/yr with little internal deformation, largely in response to the northward push of the SNGV block at its southern boundary. In contrast, the Franciscan complex is accommodating high NNW-directed and NE-directed shortening strain produced by MCC-related shortening and subduction coupling respectively. This composite tectonic regime can explain the style of faulting within and west of the KMP. Associated with this MCC crustal thickening, seismic tomography imagery shows a region of low velocity material that we interpret to represent crustal flow and injection of Franciscan crust into the KMP at intracrustal levels. We suggest that this MCC-related crustal flow and injection of material into the KMP is a relatively young feature (post ~ 5 Ma) and is driving a rejuvenated period of rock uplift within the KMP. This scenario provides a potential explanation for steep channels and high relief, suggestive of rapid erosion rates within the interior of the KMP.